(untitled) (CIPEEX, 2025)
The Brazilian prison system faces numerous difficulties when it comes to inmates’ access to education. Existing legislation provides for the right to education in prisons, but its application is hampered by a lack of investment in public policies and a lack of guarantees from the judicial authorities. The aim of this study was to analyze the difficulties faced by the Brazilian prison system when faced with the challenge of education in this context. The methodology used in this study is a theoretical reference. It was observed that among the challenges, the overcrowding of units, inadequate infrastructure, lack of resources, lack of qualified professionals and security restrictions are some of the main difficulties faced by the education system in prisons. Despite these difficulties, there are some public policies that seek to guarantee access to education in prison units, such as the National Program for Restructuring and Equipping Prison Units (PRONASCI), the National Program for Access to Technical Education and Employment (PRONATEC), the University for All Program (PROUNI), the National Program for Education in Prisons (PNEP) and the Começar de Novo Project. Another aspect is that the education of young people and adults in the prison system is of great importance in the re-socialization of inmates, contributing to their reintegration into society and reducing criminal recidivism. Education can be seen as a means of ensuring that inmates are treated with respect and have the chance to develop as individuals. In order to guarantee effective compliance with the laws and regulations governing access to education in Brazilian prisons, measures must be put in place to encourage and guarantee the provision of educational courses and activities. Among these measures, we can highlight the creation of programs to encourage education, the development of specific public policies to promote access to education in prisons, the training of education professionals and strict supervision by the competent authorities.